Z-scan analytical expressions for weak thick nonlocal nonlinear media. Issue 13 (28th July 2020) - Torres Romero, R.; Méndez Otero, M. M.; Arroyo Carrasco, M. L.; Martínez Irivas, B. A.; Iturbe Castillo, M. D.
Abstract : Analytical expressions for the on-axis normalized transmittance and total transmittance z-scan of thick nonlocal nonlinear media illuminated by a Gaussian beam are obtained in this paper. The corresponding thin media transmittance expressions and the distributed lens method are used together with the assumption that the nonlocal media exhibits weak nonlinear absorption and refraction in order to obtain the formulas. The obtained expressions enable the consideration of different degrees of nonlocality and the reproduction of the results reported for local media.